A location science model for the placement of POC CD4 testing devices as part of South Africa's public healthcare diagnostic service delivery model - Oosthuizen, Louzanne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MEng)--Stellenbosch University, 2015.